IMPLEMENTASI METODE UMMI DALAM MENINGKATKAN KEMAMPUAN MEMEBACA AL-QUR’AN DI SDIT INSAN HARAPAN KARAWANG - Isti Khotimah Khotimah (Universitas Islam Madura, 2023)
The various implementations of learning the Qur'an have its own charm for the success of learning the Qur'an, including the Ummi learning method which later became one of the reasons researchers conducted a study. The aims of this study are: 1) to describe and analyze the implementation of the Ummi method in improving the ability to read the Koran, 2) to describe and analyze the advantages and disadvantages of the Ummi method in improving the ability to read the Koran, 3) to describe and analyze the factors supporters and obstacles to the use of the Ummi method in improving the ability to read the Koran. This research uses a qualitative approach with a qualitative descriptive research type. Data collection was carried out using observation techniques, interviews, and documentation. The data analysis used is descriptive qualitative data analysis technique. The results showed that: 1) The implementation of the Ummi method at SDIT Insan Harapan used the Student Center approach, 2) The Ummi method had advantages in strategy and management, 3) the supporting and inhibiting factors that occurred in the application of the Ummi method came from within (intern) and also from the outside (external). Therefore, this research has implications for improving the learning of the Qur'an by making the results of this research additional experience and additional knowledge so that later learning the Qur'an becomes more interesting and better.